COVID-19 nationwide lockdown and it's emotional stressors among Malaysian women. Issue 3 (3rd July 2021) - Balakrishnan, Vimala; Mohamad Nor, Azmawaty; Zainal, Nor Zuraida
ABSTRACT: This study examines the prevalence rate of emotional distress and identifies its stressors among Malaysian women during the COVID-19 nationwide lockdown. Self-administered questionnaires based on previous studies and the Depression Anxiety and Stress Scale – 21 were distributed online, resulting in the recruitment of 1, 793 women aged more than 24 years old. Emotional distress was prevalent among the women (37%; N = 669). Marital Issues, Financial Issues, Living Condition, Emotion and Working from Home significantly predicted emotional distress whereas Working on Site did not. We recommend psychological support and intervention strategies to help the affected women.